PRODUCTION OF FLAMMABLE PAINTS BASED ON SILICONE AND LIQUID GLASS - Akhmedov Khafiz Ibroimovich (American Journals Publishing, 2024)
In this work, a substance obtained on the basis of silicone and liquid glass, which is added to the composition of various lacquer materials and increases their fire resistance, was analyzed. The same environment was created in laboratory conditions and the level of protection of the refractory material was studied.
Keywords: Derivatography, thermostable, level of protection, flammability, burning speed, efficiency